2022
DOI: 10.1101/2022.06.21.22276691
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep-learning-based automatic detection of pulmonary nodules from chest radiographs

Abstract: Objective: To assess a deep learning-based artificial intelligence model for the detection of pulmonary nodules on chest radiographs and to compare its performance with board-certified human readers. Methods: For this retrospective study, 308 chest radiographs were obtained between January 2019 to December 2021 from a tertiary care hospital. All radiographs were analyzed using a deep learning AI model called DxNodule AI Screen. Two expert board-certified radiologists established the ground truth, and 11 test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…In 2022, Kufel et al concluded in their systematic review that, with appropriate modifications, the developed AI tools could be utilized to diagnose other diseases related to chest organs in the future [ 9 ]. This hypothesis has now been confirmed, as multiple deep-learning (DL) technologies are currently being used to assist in triaging and detecting different chest anomalies, including pneumonia, pleural effusion, pulmonary nodules, tuberculosis, and pneumothorax [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Rayvolve, developed by AZmed (Paris, France) is a DL-based AI tool developed in a multi-centric environment.…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, Kufel et al concluded in their systematic review that, with appropriate modifications, the developed AI tools could be utilized to diagnose other diseases related to chest organs in the future [ 9 ]. This hypothesis has now been confirmed, as multiple deep-learning (DL) technologies are currently being used to assist in triaging and detecting different chest anomalies, including pneumonia, pleural effusion, pulmonary nodules, tuberculosis, and pneumothorax [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Rayvolve, developed by AZmed (Paris, France) is a DL-based AI tool developed in a multi-centric environment.…”
Section: Introductionmentioning
confidence: 99%